PENGARUH TINGKAT PENDIDIKAN, PENGALAMAN KERJA DAN PRESTASI KERJA TERHADAP PENGEMBANGAN KARIR KARYAWAN PADA CV. PONDOK ANTIK - Putu Diah Sri Ayuni; I Wayan Sujana; Ni Nyoman Ari Novarini (Program Studi Manajemen Fakultas Ekonomi dan Bisnis Universitas Mahasaraswati Denpasar., 2022)
Career development plays a role in improving one's career from one level to another as long as employees work in the company. Career development needs serious attention for the organization by increasing the level of education, work experience and work performance within the company in order to achieve the goals within the company. This study aims to examine and obtain empirical evidence of the effect of education level, work experience and work performance on the career development of CV. Pondok Antik. This research was conducted at CV. Pondok Antik with a sample of 36 employees. The sampling technique in this study was using the census method. Collecting data by distributing questionnaires using a Likert scale with a score of 1-5. The data analysis technique used in this study is a multiple linear analysis technique with the Statistical Package Social Science (SPSS) version 25 test. The results of this study indicate that the level of education, work experience and work performance have a positive and significant impact on the career development of CV. Pondok Antik. Future researchers are expected not to stick to the factors in this study, but can add other factors that might influence career development.